Measuring Substitution Patterns in the Attention Economy: An Experimental Approach. - Aridor, Guy (RAND Journal of Economics (Wiley-Blackwell))
Substitution patterns are a crucial input to antitrust analysis, but measuring them for free digital products has proved difficult due to the lack of price variation. I measure substitution patterns by installing software on experimental participants' Android phones that restricts access to Instagram or YouTube—generating variation in choice sets—and monitoring how participants reallocate their time. I find that participants substitute to multiple product categories in both restrictions but also substantially for nondigital activities. These results imply that using product characteristics as a proxy for relevant markets may incorrectly specify the relevant set of substitutes in these contexts.